THE NORTH ATLANTIC AIR-TRAFFIC CONTROL SYSTEM: ECONOMIC ANALYSIS OF PROPOSED CHANGES - Skaggs,Allen H.; Asher,Norman J.; Halfyard,Richard; Parker,Elizabeth (1965)
The study is a cost-benefit analysis to determine the economic impact of implementing certain FAA-specified technical changes to the North Atlantic Air-Traffic Control System. As such, it attempts to determine which system would afford the maximum benefit to the community of countries who provide and use the system. Accordingly, it recommends which among the technically feasible changes in facilities, services, and procedures are economically justified. Two basic types of changes were proposed: additional ground equipment to increase the capacity of the transition areas, and reduction of separation criteria in the oceanic area. The study shows the extent to which various reductions of separation criteria in the oceanic area would reduce the cost of aircraft diversions. Equipment changes in the transition areas are designed to increase the traffic-handling capacities of these areas and thereby to reduce the cost of aircraft delays during peak-flow periods. The study concludes that non-automated surveillance radar coverage should be extended over the entire transition area. (Author)